Ultrastructure of digestive cells in stingless bees of various ages (hymenoptera, apidae, meliponinae) - Serrão, José Eduardo [UNESP]; Da Cruz-Landim, Carminda [UNESP] (My University, 1996)
The ultrastructure of digestive cells of newly emerged, nurse and forager worker bees is described. Newly emerged bees have the endoplasmic reticulum characteristically in whorls and stacks as well as in parallel arrays of smooth endoplasmic reticulum. Nurse bees have spherits, autophagic vacuoles, lysosomes and multivesicular bodies. Forager bees have many cells with disorganized cytoplasm containing vacuoles, lamellated bodies, lipid inclusions, microbodies and intranuclear crystalloid inclusions. The basal cell region stays essentially unchanged. The changes observed are discussed in relation to previous observations on other insect species.
Keywords: Age; Digestive cell; Midgut; Stingless bees; Ultrastructure